Penerapan Ekonomi Syariah Pada Pengelolaan Yayasan Nusa Bangsa Podokaton Pasuruan - Sucipto, Adi (ITB AAS INDONESIA Surakarta, 2024)
This research describes the implementation of Islamic economics in the management of Nusa Bangsa Foundation in Podokaton Pasuruan. This type of research falls under qualitative research using a case study approach. The data collection procedure for this research involves conducting interviews with respondents. The data analysis utilized the Miles and Huberman model, and the validity of the data was tested using source triangulation, the use of reference materials, and member check. Nusa Bangsa Foundation is evaluated to have implemented Islamic economics. The foundation has implemented programs such as I Ana Maslahah, scholarships for orphans, and providing logistical and non-logistical assistance to the surrounding community. In other words, Nusa Bangsa Foundation has been applying Islamic economics. Employees working at Nusa Bangsa Foundation do not receive salaries but rather bisyaroh (financial assistance). The compensation they receive depends on the financial condition of the foundation. Apart from the regular contributions from students, Nusa Bangsa Foundation has income sources from Operational School Assistance Fund, business activities providing meals and school uniforms, and Logistics Assistance from several local factories. The Accountability Report Letter conducted by Nusa Bangsa Foundation still does not use complete reporting. The reports used are limited to the General Ledger.